Comparaison de trois programmes de musculation chez des joueurs de squash de haut niveau - Sciberras, P.; Ginoux, J.-M. (Science & Sports, 2019)
Aims: We have compared three types of strength training programs: heavier weights (G1), lighter weights (G2) and body weights (G3) for 15 elite squash players performing a specific and a non-specific test. Results: Average increase in total load: 16 % (G2)<30.3 % (G1)<68 % (G3). Gain in specific test: 1.8 % (G1)<4.9 % (G3)<9.6 % (G2). Gain in non-specific test: 2.1 % (G1)<4.6 % (G3)<5.1 % (G2). Coefficient of Performance: 1.4 (G1)<1.5 (G3)<2.9 (G2). Conclusion: This preliminary study shows that heavier weight training is not appropriate to physical preparation of elite squash players and that body weight training is better for health because it is less prone to accidents.